Participatory selection of Hibiscus sabdariffa L. landraces in Burkina Faso: characteristics of interest and selection criteria for leaves - Zerbo, Clémence; Nanema, Kiswendsida Romaric; Kiebre, Zakaria; Kiebre, Mariam; Tietiambou, Fanta Reine Sheirita; El Bilali, Hamid; Acasto, Filippo; Nanema, Jacques; Sawadogo, Mahamadou (Frontiers in Horticulture, 2026)
IntroductionHibiscus sabdariffa L. is an economically important and widely adopted crop in Burkina Faso. Yet its production is constrained by the lack of improved, locally adapted varieties. This study used a participatory variety selection approach to identify preferred landraces and selection criteria across two agroecological zones: Sudanian and Sudano-Sahelian.MethodsThe evaluation of landraces/accessions was carried out using an ordinal rating system, assigning scores ranging from 9 (most preferred accession), through 7 (very interesting), 5 (moderately interesting), 3 (less interesting), to 1 (least interesting). Landraces considered undesirable were specifically evaluated using negative scores of −5, −3, and −1, reflecting the degree of rejection expressed by the participants.ResultsParticipatory selection involved 126 stakeholders (75.4% women), including producers (37.3%), consumers (30.9%), processors (16.7%), and traders (15.1%). The findings showed that 130 accessions (81.25%) were positively selected across zones, with traits such as leaf size, tenderness, absence of pubescence, market value, and drought tolerance being prioritized. Preferences differed significantly by agroecological zone, ethnicity (p < 0.001), age group, and actor role (χ² = 360.21, p< 0.001). Two accessions (CKK1 and CKN5) were consistently ranked at the top, with index scores of 0.0441 and 0.0428, respectively. In contrast, accessions like CKO2 and HBB3 were most rejected due to poor agronomic and culinary traits. The analysis showed that only 30% of the selected accessions were shared between the two zones.ConclusionThese results highlight the potential value of participatory selection in identifying varieties that are well-adapted, socially acceptable, and potentially more resilient for underutilized species in West Africa.